A multidimensional strategy to rapidly identify the chemical constituents in Shengxian Decoction by using ultra‐performance liquid chromatography coupled with ion mobility spectrometry quadrupole time‐of‐flight mass spectrometry. Issue 16 (24th July 2022) - Wang, Meiyuan; Li, Hanlin; Gao, Yang; Li, Yanyi; Sun, Yuzhen; Liu, Shu; Liu, Zhongying
Abstract : As a well‐known traditional Chinese medicine formula, the chemical constituents of Shengxian Decoction still remain unclear due to its complexity. In this study, a multidimensional strategy based on ultra‐performance liquid chromatography coupled with ion mobility spectrometry quadrupole time‐of‐flight mass spectrometry and informatics UNIFI platform was applied to achieve rapid and comprehensive identification of the complex composition of Shengxian Decoction. Data‐independent acquisition, fast data‐directed analysis, and high‐definition MS E were used to obtain more and cleaner mass spectrum information. As a result, a total of 120 compounds including 74 saponins, 17 flavonoids, 7 cinnamic acid derivatives, 8 triterpenoids, and 14 others were identified or tentatively characterized by high‐resolution molecular mass, fragment ions, and collision cross‐section values. Furthermore, high‐definition MS E was used to identify six pairs of co‐eluting isomers that could not be detected from conventional data‐independent acquisition and fast data‐directed analysis. This research strategy has a certain potential for the analysis of other compound formulae and lays the foundation for the study of traditional Chinese medicine efficacy.